The Safety of Using Large Amount (30 cc) of Onyx (Ethylene-vinyl Alcohol Copolymer) for the Treatment of Large Type II Endoleak after Endovascular Repair of Abdominal Aortic Aneurysm - Namazi, Mohammad Hasan; Khaheshi, Isa; Serati, Ali Reza; Movahed, Mohammad Reza (International Journal of Angiology, 2016)
Endovascular aneurysm repair (EVAR) is associated with late complications including the development of endoleaks as major complications. Type II endoleak is the consequence of collateral retrograde flow from the aortic branches; generally from the lumbar arteries, inferior mesenteric artery, or middle sacral artery. The method and the ideal timing for the treatment of endoleaks remain controversial. We are presenting a case of successful treatment of a large type II endoleak using embolization with large amount of Onyx copolymer via a percutaneous transfemoral route without any adverse outcome. A significant advantage of Onyx as opposed to glue is that it may be injected for a long period of time (20–60 minutes) with a lower risk for microcatheter entrapment. This case report suggests that much higher amount of Onyx can safely be used if needed to seal large endoleaks without adverse event.
Keywords: endoleak; transcatheter intervention; aortic aneurysm; complications; stenting; aortic endograft; endovascular aneurysm repair; aneurysmal abdominal aorta